The Interactive Sphere for Three-Dimensional Control in Games and Virtual Reality - Brizolara, Paulo L. S.; Miranda, Leonardo Cunha de; Vasiljevic, Gabriel Alves Mendes; Menezes, Bruna Camila de (Journal on Interactive Systems, 2023)
In electronic games, the controller is the mean through which the player can interact with the game’s virtual world, being an essential factor in all of the user experience. New controllers may, therefore, completely modify the player experience, also serving as a tool to investigate new ways of interacting with interactive systems of various purposes. In this context, this paper presents the Interactive Sphere, a spherical device to be employed specially with games and virtual reality environments. This novel device combines the pressing of certain regions of the sphere with gestural interaction, in addition to providing haptic, auditive and visual feedback. The paper describes all of the rationale behind the decisions taken during the design and development process of the device, in addition to the techniques employed for implementing the detection of the acts of pressing and moving the Interactive Sphere. In this project, accessible, low-cost materials and techniques were prioritized, which could be more easily adapted to other contexts. We envision that the lessons learned and the guidelines derived from its design and development process may assist in the idealization and construction of new ways of interacting, by providing a set of methods, techniques and technologies that were employed in the development of a new physical artifact of interaction presented in this work.